Segmental Phonemes of Minangkabaunese Language Spoken in Indropuro Dialect - Peri Dani Putra; Hermawati Syarif; Leni Marlina (Universitas Negeri Padang, 2018)
AbstractEven though Indropuro dialect is a variation of Minangkabau language, they both have basic difference such as in Segmental phoneme. Hence, this research investigates the segmental phonemes of Indropuro dialect in Pesisir Selatan and how it is different from standard Minangkabaunese. The aim of this research is the identification and the distribution of consonant, vowel, and diphthong sound. Descriptive method is used as the methodology of this reearch. In this research, the writer uses interview with talk face by face strategies to collect the data. The result of this research shows that there are 31 phonemes of Indropuro dialect. They are divided into 20 phonemes consonant; /p/, /b/, /t/, /d/, /č/, /ǰ/, /k/, /g/, /?/, /s/, /h/, /m/, /n/, /ῆ/, /ŋ/, /r/, /l/, /w/, /ɰ/, and /y/, 6 phonemes vowel; /a/, /i/, /u, /e/, /o/, and /ǝ/, and 5 diphthongs; /Ia/, /ay/, /aw, /ua/, and /uy/. Moreover, the distributions of consonant, vowel, and diphthong sounds have variant distribution. Some of the consonant and the vowel have complete distribution, but all diphthongs are incomplete distribution. It is different from standard Minangakbaunese, which has 32 phonemes; 20 consonants, 5 vowels, and 7 diphthongs. The result shows that there are differences of them. It is because Indropuro dialect is not fully the same with standard Minangkabaunese even though they are in the same langauge. Based on that fact, it can be concluded that the segmental phoneme of a dialect in Indropuro is not fully the same with the standard one.